2018
DOI: 10.1017/s1751731117003251
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurements of localized fat accumulation in Shetland pony mares fed a normal v. a high energy diet for 2 years

Abstract: Health risks associated with obesity are more likely a factor of the localization of fat excess, rather than of elevated BW per se. The aim of this randomized controlled clinical trial was to determine the effect of a long-term high energy diet on BW, fat accumulation and localization. Eight Shetland pony mares, 3 to 7 years old, were randomly divided into a control and a high energy (HE) diet group fed either maintenance or double maintenance energy requirements (200% net energy (NE)) for two consecutive summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
3
16
2
Order By: Relevance
“…As expected, the hypercaloric intake over two years induced significant increases in BW, BCS, CNS and fasting serum insulin in ponies and horses. However, the achieved BW gain was less than expected in the context of previous research by Carter, McCutcheon, et al (2009) and Siegers, de Ruijter‐Villani, van Doorn, Stout, and Roelfsema (2018) in which the excess energy intake was provided by approximately 60% concentrate and 40% roughage. In contrast, the energy intake in the current study was provided by 40% concentrate and 60% roughage.…”
Section: Discussioncontrasting
confidence: 54%
“…As expected, the hypercaloric intake over two years induced significant increases in BW, BCS, CNS and fasting serum insulin in ponies and horses. However, the achieved BW gain was less than expected in the context of previous research by Carter, McCutcheon, et al (2009) and Siegers, de Ruijter‐Villani, van Doorn, Stout, and Roelfsema (2018) in which the excess energy intake was provided by approximately 60% concentrate and 40% roughage. In contrast, the energy intake in the current study was provided by 40% concentrate and 60% roughage.…”
Section: Discussioncontrasting
confidence: 54%
“…The decrease in mean BCS of the control group by 1 unit during year 1, despite a mean ± SD increase in BW of 6.2% ± 2.1%, could be explained by growth in the young group of ponies and possibly loss of muscle mass because of decreased exercise during the experimental period. A previous study reported measuring fat depths SC and retroperitoneally in some of the ponies used in our study, and found no significant changes in ultrasound detectable fat reserves in year 1, suggesting that the decrease in BCS in control ponies might not be related to fat loss alone 15 . However, the first measurements in that study were performed 12 weeks after starting the diet, and it possible that some fat loss preceded this first measurement.…”
Section: Discussionmentioning
confidence: 48%
“…Mean ± SD BCS of the HE group did, however, decrease by 1 unit from BCS 8 ± 1 to 7 ± 1 over the winter period. A previous study reported a decrease in withers and axillary fat thickness in the HE group over the winter period 15 . However, retroperitoneal fat depth did not decrease appreciably.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Despite the differences between ponies and horses, the majority of our equines did not develop steatosis within two years of BW gain. It has been described in Shetland ponies that subcutaneous tissue expandability is limited, while the expansion of the retroperitoneally adipose tissue proceeds (Siegers et al, 2018). It is one possible explanation that the expandability limit of the subcutaneous adipose tissue was not reached in the present study and therefore, fat was not stored extraordinary in retroperitoneal and intraabdominal sites like the liver.…”
Section: Discussionmentioning
confidence: 52%